Evaluating Local News on the Radio: A National Survey of Radio Station Executives. (December 2017) - Wu, Lu
News radio stations function as major sources of local news and information for their listeners, but radio stations across the United States are facing unprecedented challenges with constant drops in advertising revenue and decreasing numbers of stations devoted to an all-news or talk format. A national survey of news radio station executives from stations in different-sized markets found that stations in smaller markets were likely to broadcast a greater percentage of locally produced content compared to syndicated or outsourced content than stations in larger markets. Ownership structure, such as whether a smaller station was owned independently or by a large media conglomerate, did not appear to have an effect on the levels of local programming.